PEMODELAN PEMASANGAN PENYANGGA SEMENTARA MENGGUNAKAN PERANGKAT LUNAK PHASE 2 PADA HEADRACE TUNNEL CHAINAGE 155 M – 265 M DI PLTA TULIS KABUPATEN BANJARNEGARA, JAWA TENGAH - Muhammad Rais Fathoni (Program Studi Teknik Geologi, Fakultas Teknik, Universitas Diponegoro, 2013)
The tunnel is a copy below the ground or mountains. The tunnel was built aims to ensure a continuity of a system in theform of the transfer or objects from one place to another. Tulis Hydro Power Station is located in the Village Sokaraja,District Pagentan, Banjarnegara regency, Central Java. In the construction of Tulis Hydropower, made headrace tunnelthat serves as a time tunnel leading Merawu upstream dam plan Maung. In the construction of the tunnel, it is necessary as an alternative modeling in analysis and evaluation. Finite elementmethod is a numerical solution method, which in geomechanics used to determine the stress field and the displacementof rock mass modulus of elasticity or deformation if known by the behavior of the rock mass deformation is applied.Phase software program is a program designed for the purpose 2D finite element analysis of the process of excavation.Rock mass displacement in the tunnel was calculated using a software program Phase2. Meanwhile, as a supporter ofthe parameter values used to obtain the required form Roclab software. The parameters used in the calculation includethe tunnel geometry, boundary conditions, the main stress on the tunnel, geological conditions, the material around thetunnel, physical and mechanical properties of rocks, rock strength parameters that include the type material and thefailure criteria, the installation of a tunnel support along the physical and mechanical properties of the tunnel support . Tunnel support systems were installed in the tunnel includes rockbolt, wire mesh and steel support. While theinstallation of a tunnel support modeling used in the form rockbolt, shotcrete and liner. Determination of a tunnelsupport combinations based on the values and classes that are the result RMR rock mass classification. Simulation results show the total displacement of the excavation to be done after the installation of the a tunnel supportis as follows: 1. Simulation results chainage 198 m to the rock mass class IIIb, elastic material types for m 0.0117161 - 0.0113736 m2. Simulation results chainage 205 m to the rock mass class IIIa, elastic material types for m 0.0122892 - 0.0119034 m3. Simulation results chainage 230 m to the rock mass class IIa, elastic material types for m 0.0119481 - 0.0116411 m4. Simulation results chainage 250 m to the rock mass class IIb, elastic material types for m 0.0103595 - 0.0100815 mBased on the fourth simulation results show the number of damaged elements ranging from 8 to 23 damaged elements. The simulation results based on the finite element indicates stability can be said to be stable tunnel.